Zabawy i zabawki dzieci w tle kultury współczesnej = Children`s games and toys in the background of contemporary culture - Ferenz, Krystyna (Zielona Góra ; Skarbona: Stowarzyszenie Polskich Muzyków Kameralistów)
Human is in great manner a result of the times and culture to which he belongs. Each culture creates functioning patters and transfers it with generations. Playing is port of culture. Children live in social world of their parents. Everyday life is for a child an experience of the world. Behavioural patterns delivered in pre-school age one may observe socio-cultural determinism, presented by the concept of P. Bourdieu.
Keywords: zabawy; zabawki; dziecko w wieku przedszkolnym; wzory zachowań; games; toys; pre-school period; patterns of behaviour